Polycyclic Aromatic Hydrocarbons Burden of Meats Singed with Different Fuel Sources from Abattoirs in Ghana and Associated Cancer Risk Assessment - Prosper Manu Abdulai; Chika Ossai; Anthoneth Ndidi Ezejiofor; Chiara Frazzoli; Joaquim Rovira; Osazuwa Clinton Ekhator; Caleb Kesse Firempong; Orish Ebere Orisakwe (Environmental Health Insights)
This study evaluated the concentrations of polycyclic aromatic hydrocarbons (PAHs) and the carcinogenic risks of cattle and goat meats singed with either firewood, Liquefied Petroleum Gas (LPG) or tyres from five cities in Ghana. The meat samples, before and after singeing, as well as after scraping and washing, were collected from abattoirs and sent to Clinical Analysis Laboratory (Can-Lab) of Kwame Nkrumah University of Science and Technology (KNUST) for PAH analysis. Tyre-singed meats exhibit significantly higher PAHs concentrations ( P  = .01304) compared to those singed with firewood and LPG. Benzo[a]pyrene was the predominant PAH in tyre-singed cattle and goat meats, with concentrations of 23.1 mg/kg and 12.16 mg/kg, respectively. Washing singed meats reduced PAH levels, yet tyre-singed samples retained higher and dangerous concentrations than those singed with other fuels. Statistical analysis using ANOVA confirmed a significant effect of fuel type on PAH16 concentrations ( P  = .01304). The Tukey HSD test indicated a significant difference between LPG and tyre ( P  = .0105). Estimated daily intake (EDI) calculations highlighted potential health risks, particularly from tyre-singed meats, which exceeded regulatory limits set by health authorities. The findings emphasize the health hazards associated with consuming meats singed with tyres in Ghana and underscore the need for stringent regulatory measures and public awareness to mitigate PAH exposure.